EFFECTS OF ETHANOL ON MOUSE EMBRYONIC STEM CELL DIFFERENTIATION - Yamashita, Akihisa; Asahi, Junpei; Takaki, Miyako; Nakashima, Tamiji; Kamiwada, Keita; Watanabe, Shota; Murakami, Daisuke; Hirano, Takeshi (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Chronic alcohol consumption during gestation causes fetal malformations, termed fetal alcohol syndrome (FAS). We conducted the present study to clarify the mechanism underlying alcohol consumption-induced malformations. Methods: First, the effects of ethanol on the viability of cell lines, such as EB3 (undifferentiated mouse embryonic stem (ES) cells), 3T3-Swiss albino, Neuro-2a, NCTC Clone 1469, and UBE6T-15, were determined. Furthermore, ethanol-induced cell death patterns were analyzed by the annexin V-Cy3.18 (AnnCy3) immune fluorescent method. Second, the effects of ethanol on ES cell differentiation were assessed by the embryoid body (EB) model. The formation of an EB, accompanied by spontaneous pulsation derived from EB3 cells, was monitored. EB3 cells were cultured in hanging drops of media containing 0-5% ethanol for 8 days. We then analyzed the EB formation grade by counting the EBs accompanied by spontaneous pulsation in four categories and by monitoring the expression of differentiation marker genes: connexin43, GATA4, c-kit, Î±-SMA, and Oct-3/4. Results: EB3 cells were more sensitive to alcohol than the other four cell lines, and that ethanol-induced death of EB3 cells matched the apoptosis pattern. There were no obvious differences in the formation rates of EBs with pulsation among all ethanol-treated groups. However, c-kit gene expression was significantly decreased in the EBs treated with 3 and 5% ethanol, in comparison to the control EBs. Conclusion: Collectively, the present study suggested that ES cells are more sensitive to ethanol than differentiated cells, and that ethanol-induced down regulation of c-kit expression might be involved in alcohol-induced malformations.